2022
DOI: 10.3389/fcimb.2022.922189
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs and myocardial involvement severity in chronic Chagas cardiomyopathy

Abstract: BackgroundChronic Chagas Cardiomyopathy (CCM) is characterized by a unique pathophysiology in which inflammatory, microvascular and neuroendocrine processes coalesce in the development of one of the most severe cardiomyopathies affecting humans. Despite significant advances in understanding the molecular mechanisms involved in this disease, scarce information is available regarding microRNAs and clinical parameters of disease severity. We aimed to evaluate the association between circulating levels of six micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Further, although the exact mechanism by which miRNAs are involved in ChCM pathophysiology remains unclear, studies have revealed that the biogenesis of miRNAs implicated in cardiac physiology is affected by T . cruzi infection, and thus miRNAs could potentially serve as prospective biomarkers for ChCM [ 11 14 , 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, although the exact mechanism by which miRNAs are involved in ChCM pathophysiology remains unclear, studies have revealed that the biogenesis of miRNAs implicated in cardiac physiology is affected by T . cruzi infection, and thus miRNAs could potentially serve as prospective biomarkers for ChCM [ 11 14 , 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of ChCM, various studies have explored miRNAs’ expression profiles in patients and identified specific miRNAs that are dysregulated in cardiac tissues [ 11 14 ]. These findings suggest that miRNAs could be potential biomarkers for diagnosing ChCM and monitoring disease progression [ 12 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since miRNA expression changes during pathogen infection, they have been proposed as a tool for the prevention, diagnosis, prognosis, treatment, and control of parasitic diseases [ 16 , 22 , 23 , 24 ]. In addition, several miRNAs have been suggested as biomarkers of some parasitic diseases’ different phases and severity [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…BNP and NT-proBNP, well-known markers be associated with cardiac dysfunction ( 14 ), have been associated to Chagas cardiomyopathy ( 15 , 16 ), but are not specific to this pathology. Others markers, including miRNAs ( 17 , 18 ), cytokines ( 19 ) or metalloproteinases ( 20 ) have been proposed as biomarkers for CCC, but no confirmation has been made in a test cohort at this time. The only diagnosis of CCC currently in place is a clinical diagnosis, which is difficult to access for the most remote populations.…”
Section: Introductionmentioning
confidence: 99%